Strangulated paraduodenal hernia: about an observation - Matteucci, Pablo; Puig, Ana M; Piedra-Buena, Luis (Cirugía del Uruguay, 1973)
Paraduodenal herniation is a rare disease and is generally due to malformations which exaggerate or deepen duodenal fossae. It only becomes apparent when a thin loop is strangled in them, as in the case presented _by the authors. Surgery was successful.